PENGARUH PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP KEJADIAN STUNTING PADA BALITA USIA 2-5 TAHUN DI WILAYAH KERJA PUSKESMAS KAPOTA KECAMATAN WANGI-WANGI SELATAN KABUPATEN WAKATOBI TAHUN 2025 - Nikmah Saro (Rena Cipta Mandiri, 2025)
Stunting is a health issue that remains a serious concern in Indonesia. The prevalence of stunting continues to increase, particularly in the working area of Kapota Health Center. Based on initial observations, there are three aspects suspected to influence the incidence of stunting in children, namely personal hygiene, availability of clean water, and exclusive breastfeeding. The aim of this study is to determine the influence of Clean and Healthy Living Behavior (PHBS) on the incidence of stunting in children aged 2-5 years in the working area of Kapota Health Center, Wangi-Wangi Selatan District, Wakatobi Regency in 2025. This research is quantitative with a case-control study design using age matching, and the sampling technique is purposive sampling, with a sample size of 15 case groups and 15 control groups. Analysis was conducted using univariate and bivariate analysis.The results indicate that the variable of personal hygiene has an odds ratio (OR) of 5.500 and a confidence interval (C) of 0.556, the availability of clean water has an OR of 1.429 and a C of 0.378, while exclusive breastfeeding has an OR of 0.400 and a C of 0.514. The conclusion of this study is that the variables of personal hygiene and the availability of clean water are aspects that influence the incidence of stunting. Furthermore, exclusive breastfeeding is a protective variable, meaning that exclusive breastfeeding does not have an influence on the incidence of stunting in children in the working area of Kapota Health Center.